MANAJEMEN DATABASE DI ERA BIG DATA: TEKNOLOGI DAN TANTANGAN - Andhini Asmita; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
The era of big data has brought significant changes in the way organizations manage and utilize data. Massive data volume, high processing speed, and diversity of data sources are the main challenges in modern database management. This article aims to examine the evolution of database management in the context of big data, highlighting the latest technologies applied, as well as the challenges faced in their implementation. This paper is written through a descriptive approach by analyzing various literature sources, such as scientific journals, books, and relevant technical documentation. The results of the study show that there are technologies used in database management, as well as the main challenges that need to be considered in implementing databases in big data environments.